2020
DOI: 10.3390/f11121272
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Briquette Produced with Torrefied Agroforestry Biomass to Generate Energy

Abstract: Agroforestry industries, such as sugar-alcohol, food, and logging, produce large quantities of waste, used to generate energy from direct burning. The application of other processes, such as torrefaction and briquetting, can increase the profits from the use of agro-industrial waste for energy generation. Briquetting is an alternative for using these wastes, allowing the compaction of the biomass, generating a biofuel with high energy density, and which is more homogeneous and easier to store and transport. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Various components, including condensable and non-condensable species added to the simulation, were identified from the pilot-scale experimental studies and the literature review provided in the supplementary material (Table S1) [10,13,14,[37][38][39][40][41][42][43][44][45]. The general input parameters used for the simulation are shown in Table 1.…”
Section: Aspen Plus™ Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various components, including condensable and non-condensable species added to the simulation, were identified from the pilot-scale experimental studies and the literature review provided in the supplementary material (Table S1) [10,13,14,[37][38][39][40][41][42][43][44][45]. The general input parameters used for the simulation are shown in Table 1.…”
Section: Aspen Plus™ Simulationmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/cleantechnol5020034/s1, Table S1: Condensable species recovered from the torrefaction of pinewood at various temperatures; Figure S1: (a-c References [10,12,15,30,[37][38][39][40][41][43][44][45]53] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The O/C and H/C ratios reduce due to the reduction in oxygen and hydrogen contents relative to the carbon content (Akogun and Waheed, 2019 ; Nunes et al 2021 ) which is an indication of the maximized mass yield and energy of biomass (Chen et al 2015 ). Moreover, torrefaction also results in reducing volatiles and moisture content through heating (Portilho et al 2020 ; Chaves et al, 2021 ). It helps to ameliorate the limitations of raw feedstocks for briquette production and upscale their qualities (Nhuchhen et al 2014 ).…”
Section: Torrefaction Pre-treatment Of Biomass For Briquette Productionmentioning
confidence: 99%
“…Emadi [ 13 ] also reported that adding 6% LDPE to the mixed biochar increased the density of wheat and barley by 1.8% and 1.7%, respectively, while adding 10% LDPE to the mixed biochar increased the compressive strength of the wheat and barley briquettes by 280% and 253%, respectively, thus greatly improving their transport and storage efficiency. Portilho [ 22 ] evaluated the physicochemical properties of eucalyptus, pine, coffee grounds, and sugarcane bagasse after torrefaction and reported that torrefaction improved biochar fuel properties and pelletization at 10.34 MPa pressure, improved the mechanical properties, and increased the energy potential of the briquettes.…”
Section: Introductionmentioning
confidence: 99%